Hubungan School Well-Being dengan Motivasi Belajar Siswa pada Mata Pelajaran IPAS dalam Perspektif Adab Belajar Islami di SDN Mulangsari III Karawang - Dikky Nugraha; Vina Febiani Musyadad; Agung Prasetyo; Nugraha, Dikky (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
This study aims to explore the level of students' School Well-Being and IPAS learning motivation, as well as to examine the relationship between the two from the perspective of Islamic learning adab at SDN Mulangsari III Karawang. Applying a quantitative approach with an ex post facto correlational design, this research involved 52 students from grades IV, V, and VI as a total sample (saturation sampling). Data collection relied on questionnaires, supported by observation and documentation. The collected data were then analyzed using descriptive statistics, normality tests, and the Spearman Rank correlation test. The results revealed a highly positive trend: the students' School Well-Being was categorized as high (mean = 29.92), as was their IPAS learning motivation (mean = 36.83). Furthermore, there was a positive, moderate, and significant correlation between the two variables (rho = 0.468; Sig. < 0.001). Broadly speaking, positive experiences in the school environment are proven to be closely related to students' drive to learn. Viewed through the lens of Islamic learning adab, School Well-Being plays a crucial role in fostering a climate that supports students' readiness, active participation, sense of responsibility, and earnestness in seeking knowledge.